Psychosocial Stressors in Patients Presenting with Depression Episodes: Psychosocial Stressors in Patients - Leghari , Naeem Ullah; Akram , Bushra; Bilal, Ahmad (Pakistan Journal of Health Sciences, 2022)
Depression is a mood disorder characterized by aversion to activities that affects a person's thoughts, behaviour, feelings, and sense of well-being. Objective: To explore the psychosocial stressors / life events and demographic variables in patients with major depression in 1st and subsequent episodes with related sociodemographic factors in each. Methods: The sample of this study was 50 consecutive in-patients with Major Depression. Detailed open-ended interview was conducted and also administered The Presumptive Stressful Life Events Scale (PSLES) to elicit psychosocial stressors and major life events in 1st episode and in the subsequent episodes. Results: showed that of the 50 subjects, majority of subjects 32(64%) were female, 13 (26%) were 26-30 years’ age group, 33(66%) belonged to urban area, 23(46%) were suffering from 3rd and more depressive episodes, 21(42%) reported positive family history, 28(56%) were suffering for 3 months. In psychosocial stressors / life events, 26% had Death of spouse, in Marital and Sexual factors 16% patients reported relationship effect with spouse in 1st, 22% in 2nd and 30% in 3rd Depressive episode and in financial difficulties 12% patients in 1st episode, 20% and 28% in subsequent episodes. Conclusions: Study concluded that there was difference of psychosocial stressors in 1st and subsequent episodes of depression.